2014
DOI: 10.1111/fwb.12461
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, movement and behaviour of native mussels during a planned water‐level drawdown in the Upper Mississippi River

Abstract: 1. Managers in the Upper Mississippi River (UMR) are using reductions in the River's water levels during summer to mimic historical water regimes and rehabilitate habitats for vegetation and other species. Concerns for the unintended effects of these actions on mussel populations threatened to halt these projects. 2. Our objective was to characterise the survival and movement of two mussel species in the UMR associated with a water level drawdown. During 2009 (no drawdown) and 2010 (0.3 m summer drawdown), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 35 publications
7
45
0
Order By: Relevance
“…The positive effect of slope on mussel densities in drawdown lakes observed in this study aligns with findings from Newton et al (2015) where high slopes tend to have lower mussel mortality under water level drawdown conditions. The positive effect of slope on mussel densities in drawdown lakes observed in this study aligns with findings from Newton et al (2015) where high slopes tend to have lower mussel mortality under water level drawdown conditions.…”
Section: Landscape and Habitat Influences On Mussel Densities And Dsupporting
confidence: 89%
See 1 more Smart Citation
“…The positive effect of slope on mussel densities in drawdown lakes observed in this study aligns with findings from Newton et al (2015) where high slopes tend to have lower mussel mortality under water level drawdown conditions. The positive effect of slope on mussel densities in drawdown lakes observed in this study aligns with findings from Newton et al (2015) where high slopes tend to have lower mussel mortality under water level drawdown conditions.…”
Section: Landscape and Habitat Influences On Mussel Densities And Dsupporting
confidence: 89%
“…Mussels can respond to drawdowns by tracking water levels via directed horizontal movement (Gough, Landis, & Stoeckel, 2012;Newton et al, 2015;Richardson et al, 2002) and permit survival during a drawdown event. Mussels can respond to drawdowns by tracking water levels via directed horizontal movement (Gough, Landis, & Stoeckel, 2012;Newton et al, 2015;Richardson et al, 2002) and permit survival during a drawdown event.…”
Section: Acute Mortality In Winter Drawdown Lakesmentioning
confidence: 99%
“…Some species have also been shown to move horizontally to deeper or shallower areas when exposed to stress (e.g. Newton, Zigler, & Gray, ), and may be able to avoid fully anoxic areas. There are currently no data on the tolerance of E .…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous research into the survival adaptations of mussels to dewatering has only focused on one of the two general responses of mussels, behavioural response (i.e., horizontal/vertical movement) (Bartsch et al., ; Gough et al., ; Newton et al., ; Galbraith et al., ; Table ) or physiological tolerance (Bartsch et al., ; Byrne & McMahon, ; Holland, ; Galbraith et al., ; Gough et al., ; Golladay et al., ; Johnson, Liner, Golladay, & Michener, ; Spooner & Vaughn, ; Table ). Gough et al.…”
Section: Introductionmentioning
confidence: 99%
“…We predict their horizontal mobility to be intermediate between equilibrium and periodic species. In respect to burrowing behaviour, studies have reported that the species with the higher desiccation tolerance tended to burrow deeper than more intolerant species (Galbraith et al., ; Gough et al., ; Newton et al., ). Accordingly, we predict that equilibrium species (with the assumed highest desiccation tolerance) will burrow deeper than periodic or opportunistic species (Table ).…”
Section: Introductionmentioning
confidence: 99%